A cry in the dark - Lewis, Beverly, 1949- (Minneapolis, Minn. : Bethany House Publishers, 1996)
Merry Hanson discovers an abandoned baby and wants to adopt it.
"Ages 11-14"--cover p. [4].
Accelerated Reader AR
Keywords: Amish -- Juvenile fiction; Friendship -- Juvenile fiction; Children -- Abandoned -- Fiction; Babies -- Fiction